Analisis Pengaruh Transformasi Digital dan Pola Perilaku Konsumen Terhadap Perubahan Bisnis Model Perusahaan di Indonesia - Ricky Oktavenus (Universitas Tarumanagara, 2019)
This study aims to determine the main factors that can influence the shifting in company business model. Based on previous research, two independent variables are obtained: digital transformation and customers behavior pattern. This is a descriptive research by using questionnaire which are distributed to 151 respondents from employee of sales division in Jakarta. Data was collected using simple random sampling method. Partial least square analysis was used for data analysis by using SmartPLS software. Outer model and inner model analysis is being done in the partial least square analysis. This study found that the influence of each variables can directly influence the company’s business model significantly.